Pengaruh Literasi Digital Dan Media Sosial Facebook Terhadap Pendapatan Usaha Rumah Tangga - Muhlis, Nurul Maghfira; Dahlan, Fadli; Majojo, Muhammad Yasin (Peneliti.net, 2025)
This research aims to determine the effect of digital literacy and Facebook social media on Umi Tum's household business income. This study uses quantitative methods. The population of the research results shows that the digital literacy variable has a positive and significant effect on income, this is indicated by a coefficient value of 0.390 with a Tcount value of 6.978> Ttable 1.971. With a significance level of (0.000) <0.05. Furthermore, the Facebook social media variable has a positive and significant effect on income, this is indicated by a coefficient value of 0.448 with a Tcount value of 8.010> Ttable 1.971 With a significance level of (0.000) <0.05 and digital literacy and Facebook social media simultaneously have a significant effect on income with Fcount 142.175> 3.04 with a significance level of 0.000 <0.05. The sample in this study was 223 active customers/consumers of the Umi Tum home business in Gurabati sub-district.